Polycystic ovarian syndrome - management and treatment - Martyna Julia Kłosińska; Agnieszka Kaczyńska (Kazimierz Wielki University, 2021)
The polycystic ovarian syndrome is an endocrine disorder with a high prevalence affecting reproductive-aged women and adolescent girls. The most common symptoms are infertility, numerous ovarian cysts, hyperandrogenism, menstrual cycle abnormalities. The disease has a great impact on patients, impairing their quality of life. Bearing that in mind, innovative therapeutic approaches are needed. We aim to describe current management and treatment concepts adopted in PCOS therapy. The analysis of previously published studies was conducted by using the PubMed, Google Scholar, and Scopus databases. Mentioned studies show that lifestyle changes may benefit PCOS therapy in multiple ways. Dietary and exercise interventions have a notable influence on women's body composition as well as biochemical parameters. The reduction of body weight or BMI is a therapeutic achievement likewise patients' contribution to managing PCOS. Pharmacotherapy provides plentiful treatment choices to adopt. Studies show that hormonal contraceptive has a significant impact on both hyperandrogenism and menstrual abnormalities. Metformin is proven to reduce BMI, improve LDL levels, and lower the risk of OHSS in women undergoing IVF/ICSI-ET. A meta-analysis proved metformin's monotherapy superiority over clomifene citrate or their combination in treating infertility. However, both substances are not recommended as the first-line choice. Regrettably, many studies mention short of evidence, lack of larger sample sizes, or insufficient duration preventing further research. The conclusion we draw is that approaches of managing and treating PCOS are constantly advancing and updating. However, there is a necessity for future studies to expand their research by gathering more data and considering diverse cases.